Lower Extremity Kinematic Waveform Analysis During a Single Leg Drop Task - Including a Single Subject Design - Nickolai JP Martonick; Youngmin Chun; Lukas Krumpl; Joshua P Bailey (North American Sports Medicine Institute, 2022)
# BACKGROUND Lower limb asymmetries may be associated with increased injury risk in an active female population. However, an appropriate method for determining these asymmetries has not been established. # HYPOTHESIS/PURPOSE The purpose of the present study was to examine the single leg drop landing (SLD) kinematic waveforms of female recreational athletes for the pelvis, hip, and knee using statistical parametric mapping (SPM). It was hypothesized that individual bilateral differences would be masked by the group analysis. # STUDY DESIGN Descriptive Laboratory Study. # METHODS The current study examined the sagittal and frontal plane pelvis, hip, and knee kinematics of nine physically active females during a SLD. To better elucidate whether asymmetries were present between right and left limbs throughout the landing phase, data were analyzed with SPM. The time-series data were comprised from initial contact to the bottom of the landing. A single subject design was also included to account for potential interindividual variability. # RESULTS At the group level there were no statistical differences between the right and left limbs of participants for all variables. The single subject design yielded at least two significant asymmetries for all participants. Six out of the nine participants had bilateral differences for all six kinematic time-series. # CONCLUSIONS The lack of significant differences at the group level may have been masked by movement variability amongst participants. For example, when considering participants with significant differences for hip flexion, four participants had greater values on the left limb and three on the right. A similar observation was made for knee flexion where three participants had significantly greater kinematic values on the left versus four on the right. Until a method is developed to adequately dichotomize lower extremities during the SLD task, a single subject design strategy be used with group analysis when making bilateral comparisons. # LEVEL OF EVIDENCE 3